An Overnight Stay Versus three Days Admission after Uncomplicated Percutaneous Nephrolithotomy: A Randomized Clinical Trial - Basiri, Abbas; Arab, Davood; Pakmanesh, Hamid; Abedinzadeh, Mehdi; Karami, Hormoz (Urology Journal, 2020)
Purpose: To evaluate the safety and efficacy of discharging patients on the first postoperative day after an uncomplicated percutaneous nephrolithotomy (PCNL). Materials and methods: after an uncomplicated successful PCNL without significant residual stone (>5mm) or any complication up to the first postoperative day, we randomly assigned patients into two groups—Group 1: overnight surgery, and Group 2: routine discharge after three days. Patients with significant residual stone on control fluoroscopy were excluded. Ninety eight and 102 patients were assigned to groups 1 and 2, respectively. Serum Hemoglobin and Cr were evaluated before the operation as well as the first postoperative day. Stone free status was evaluated using ultrasound and KUB radiography at the first postoperative day. Results: The stone and patient characteristics were not different in two groups. The preoperative and change in the hemoglobin and creatinine levels were not significantly different between the two groups. Nine patients (9.2%) in Group 1 and five (4.9%) in Group 2 were readmitted because of complications (mainly hematuria) (p=.23). Of the readmitted patients, five in Group 1 (55%), and three in Group 2 (60%) received blood transfusion (p=.87). in these patients, group 1 received 1.6±0.51 units of blood compared with 1.93±0.25 in group 2 (p=.07). All the readmitted patients did well with conservative therapy with no need for angioembolization. Conclusion: In uncomplicated PCNL with no significant residual stone, discharging the patient on the first postoperative day is safe. The outcome is comparable to a routine three-day hospital stay.